Collective Land Certification Policy as an Alternative to Land Conflict Resolution and Rural Development in Flores, Indonesia - Tolo, Emilianus Yakob Sese (UI Scholars Hub, 2018)
Since the 1980s, the Indonesian government has been highly promoting individual land certification (ILC) program as a national strategy to facilitate development. National programs like Proyek Operasi National Agraria (PRONA) and Layanan Rakyat Untuk Sertifikasi Tanah (LARASITA) are launched by the Indonesian National Land Agency (NLA) to facilitate ILC programs in rural areas. The programs have reached many rural areas in eastern Indonesia. Utilizing the combination of qualitative and quantitative research methodology by way of 30 in-depth interviews and 320 questionnaire, this research aims to evaluate the government programs on ILC in rural Flores, Indonesia. The research finds that ILC programs may have led to the increased poverty, land transactions and land speculations that boost land tenure conflicts which hinder the development in rural Flores. This research proposes colective land certification (CLC) program as an alternative for rural development.